Product Placement in Movies: Relationship Between Beliefs Towards Product Placement and Usage Behavior - Qureshi, Ishtiaq Hussain; Gul, Maleeha (Indian Journal of Marketing, 2015)
Product placement (PL) in movies is an emergent media vehicle for promoting brands and products. It is receiving a great deal of attention from both academicians and media persons. This paper presented an exploratory quantitative study that reports the beliefs of 163 college going students towards the practice of product placements and links them with product usage behavior. The study suggests that some beliefs are very useful in predicting the usage behavior and can be used potentially by marketers. A very limited number of studies have tried to explore this relationship in the past.